Pengaruh Model Problem Based Learning Di Kalangan Siswa Berkemampuan Akademik Berbeda Terhadap Kemampuan Berpikir Kritis Pada Pembelajaran Biologi - M. Danil (Peneliti.net, 2021)
The Problem Based Learning (PBL) model is a learning model that supports the development of students' critical thinking skills which is one of the competencies students must have in the 21st century. The purpose of this study was to determine the effect of the PBL model on critical thinking skills in biology learning. This study used a quasi-experimental research design. The number of research samples was 202 class X students consisting of 4 upper academic ability classes and 4 lower academic ability classes taken from 5 schools namely Bireuen 3 Public High School, Peusangan 1 Public High School, Gandapura 1 Public High School, Siblah Krueng 1 Peusangan High School and High School Country 1 Term. Determination of the sample is done by random sampling technique. Critical thinking skills data collection is done by giving an essay test. The research data were analyzed using qualitative descriptive statistics to describe the ability to think critically and statistical inferential analysis of covariates (Anakova) with a significance level of 5% which was used to test the hypothesis. The Anakova test results show that the PBL model and academic ability on students' critical thinking skills show that the p-level (0.000) < α (0.05) with a significance of 0.000 and 0.000. So it can be concluded that the PBL model influences critical thinking skills in biology learning.